A Linguistic and Culture Panorama of Interconnected Disciplines (Global Journal of Human-Social Science, 2021)
Scientifically speaking we, all know that the origins of language and culture remain unknown. Researchers relate to fossil, archeology evidence, and historical accounts in attempting to access what many scholars do think is a topic that lacks of direct evidence. However, when it comes to the languages and cultures we know today, it could be viable to investigate correlational language and cultural patterns in Applied Linguistics Studies. Thus, the present research study looks at the Spanish syntaxes [tú and usted] to highlight correlated linguistic and cultural traits. It presents an analyse of the Applied Linguistic and Culture patterns related to the subject investigated, and methodological insights based on the method developed by Edward T. Hall, a prospect that describes and analyses cultures. The research study was conducted by following suitable research protocols. This criterium involved the analysis of various research publications and Internet accredited website sources. This research study is beneficial for scholars involved and interested in conducting researchers related to Spanish Linguistic and Cultural Connectiveness Patterns.
Keywords: linguistics; sociolinguistic; sociocultural; culture; communication; methodology